Inovasi Perencanaan Keuangan menggunakan Artificial Intelligence (AI) Click Up pada UMKM Chibi-chibi Mochi - Fia Dialysa (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service aims to innovate Artificial Intelligence (AI) financial planning using the ClickUp application to improve the quality of project management, especially budgeting, thereby increasing efficiency, productivity, and better decision-making so that these MSMEs can be highly competitive in the fintech era. Artificial intelligence is a system in a machine that imitates the way humans think and act (human intelligence). One of a computer science related to the development that can imitate human expertise in carrying out certain tasks is Artificial Intelligence (AI) (Nurcholis, 2023). The program carried out is training and mentoring so that financial planning is more innovative, economical, practical, easily accessible, and has minimal errors. The problem faced by business actors is financial planning that has not been implemented properly so business targets and income targets are often not achieved. This has an impact on the sustainability of the Chibi-Chibi Mochi MSME business in the era of competition. The solution to the problem is that the community service team will provide training and mentoring on financial planning innovation using Artificial Intelligence (AI) ClickUp. The output targets to be achieved are in the form of journal publications and increasing the understanding and skills of business actors.